Pengaruh Profitabilitas, Likuiditas, Leverage, dan Pertumbuhan Aset terhadap Kebijakan Dividen - Misce Lina Rizki; Yanuar Ramadhan (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
The objective of this study is to examine the effects of profitability, liquidity, leverage, and asset growth on dividend policy among food and beverage companies listed on the IDX during 2020-2023. The dependent variable in this study is dividend policy, specifically the proxy dividend payout ratio (DPR). The independent variables, including profitability as measured by return on equity (ROE), liquidity as measured by the current ratio (CR), leverage as measured by the debt-to-equity ratio (DER), and asset growth as measured by the asset growth proxy (Growth), will also be examined. The data collection process used secondary data and employed purposive sampling. The study’s initial population included 95 samples; however, after applying the criteria, 17 were found relevant. The methods used in this study include descriptive statistical analysis, classical assumption test, hypothesis testing, and multiple linear regression analysis. The study’s results suggest that profitability, liquidity, and leverage may have simultaneous effects on dividend policy. It appears that profitability and liquidity may positively affect dividend policy, while leverage may negatively affect it, and asset growth may have no effect. It is hoped that the results of this study will provide a useful reference point for management and other relevant parties as they plan dividend policy, maintain business continuity, and make investment decisions.